Biossensores para a detecção de agentes infecciosos e análise da qualidade de alimentos - Ribeiro, Sandro Henrique Dias (2024)
Infectious diseases represent risks to the population and challenges for healthcare services. An example is cytomegalovirus, a pathogen from the Herpesvirus family that is easily transmissible and capable of causing infection and complications, especially in pregnant women and immunosuppressed individuals; another example is Escherichia coli O157:H7, which is associated with foodborne illnesses, mainly due to the production of toxins that can lead to hemorrhagic diarrhea, Hemolytic-Uremic Syndrome (HUS), and even death. Thus, efficient detection of the pathogen is crucial both in assessing food quality and in the diagnosis, monitoring, and/or treatment of infectious diseases. The development of biosensors assists in identifying these pathogens that affect public health due to the advantages presented by such devices, such as low cost, specificity, sensitivity, selectivity, rapidity, possibility of miniaturization, and portability. Considering this, the present doctoral thesis aimed to develop two electrochemical genosensors for the detection of Cytomegalovirus and Escherichia coli O157:H7, by immobilizing a specific DNA probe for each pathogen on graphite electrodes modified with nanomaterials derived from amino acids. This work contributes to the ongoing efforts to build increasingly simple and economical biosensors, crucial for various applications, including medical diagnostics, food safety, and environmental monitoring.